Transplacental Transmission of Plasmodium falciparum in a Highly Malaria Endemic Area of Burkina Faso - Alphonse Ouédraogo; Alfred B. Tiono; Amidou Diarra; Edith C. Christiane Bougouma; Issa Nébié; Amadou T. Konaté; Sodiomon B. Sirima (Journal of Tropical Medicine)
Malaria congenital infection constitutes a major risk in malaria endemic areas. In this study, we report the prevalence of transplacental malaria in Burkina Faso. In labour and delivery units, thick and thin blood films were made from maternal, placental, and umbilical cord blood to determine malaria infection. A total of 1,309 mother/baby pairs were recruited. Eighteen cord blood samples (1.4%) contained malaria parasites (Plasmodium falciparum). Out of the 369 (28.2%) women with peripheral positive parasitemia, 211 (57.2%) had placental malaria and 14 (3.8%) had malaria parasites in their umbilical cord blood. The umbilical cord parasitemia levels were statistically associated with the presence of maternal peripheral parasitemia (OR=9.24, 𝑃≪0.001), placental parasitemia (OR=10.74, 𝑃≪0.001), high-density peripheral parasitemia (OR=9.62, 𝑃≪0.001), and high-density placental parasitemia (OR=4.91, 𝑃=0.03). In Burkina Faso, the mother-to-child transmission rate of malaria appears to be low.